Variable expression of CD49d antigen in B cell chronic lymphocytic leukemia is related to disease stages - (:unkn) unknown (NATURE PUBLISHING GROUP, 1996)
We have investigated the expression of the dual specific adhesion molecule, VLA-4 (CD49d/CD29) on lymphocytes obtained from 62 patients with B-CLL and compared it with normal controls, patients with other hematological malignancies, and umbilical cord blood. The mean CD49d expression in patients with CLL was lower than the other group of leukemia and the CD19(+), CD5(+) cells of normal peripheral blood and umbilical cord blood (P < 0.001). The patients in RAI stage 0, I and II (early stage) had even lower CD49d expression, whereas patients in RAI stage III and IV (advanced stage) had relatively higher CD49d levels. In vitro adhesion of lymphocytes to fibronectin, being the extracellular matrix ligand of CD49d, was also investigated. Lymphocytes obtained from B-CLL were found to have lower adhesion to fibronectin than that from controls (P < 0.03). Furthermore, CD49d(low) B-CLL cells had lower adhesion to fibronectin, whereas CD49d(high) B-CLL cells showed normal adhesion ratios (P < 0.002). Further phenotypic analyses revealed the presence of myeloid markers (CD13 and CD33) in most of the advanced stage patients, although these were negative in early stage cases. Expressions of CD11a and sIgM were also low but CD11b was relatively higher in the early stages of the disease. On the basis of these results, we concluded that early stages of CLL are correlated with the expression of CD49d(low), CD11a(low), CD11b(high), CD13(-), CD33(-), sIgM(low) and also had lower fibronectin adhesion, whereas advanced stages of CLL are associated with CD(49)d(high), CD11a(high), CD11b(low), CD13(+), CD33(+), sIgM(high) and show normal fibronectin adhesion.
Keywords: CLL; CD49d; myeloid marker; adhesion; fibronectin; MARROW STROMAL CELLS; HUMAN BONE-MARROW; ADHESION MOLECULE-1; MYELOMONOCYTIC ANTIGENS; HEMATOPOIETIC-CELLS; LYMPHOMA-CELLS; INTEGRINS; FIBRONECTIN; VLA-4; BINDING